International survey of seat belt use exemptions - Weiss, H (BMJ Group, 2006)
BACKGROUND: Substantial evidence of seatbelt efficacy has been shown by several studies, and it is widely recommended that motor vehicle occupants use properly fitted seat belts. However, some (but a heretofore unknown number of) countries with national seat belt laws permit various exemptions which may lower use rates. The aim of this study was to survey the variety of exemptions to national seat belt laws. METHODS: This investigation relied on identifying respondents from national traffic safety agencies, other governmental and non‐governmental organizations, Internet searches, personal contacts, and other sources. Questionnaires were deployed through a web based survey supplemented by email and postal versions. RESULTS: Responses were received from 30 countries of which 28 (93.7%) had a national seat belt law. About two thirds (63.7%) of the 28 national laws applied to both front and back seat passengers. The leading exemption types included vehicles made before a certain year (n = 13), antique vehicles (n = 12), military vehicles (n = 11), buses (n = 9), and emergency vehicles (n = 8). Most responding countries reported one or more specific categories of individuals as exempt including those with medical exemptions (n = 20), taxi drivers (n = 11), police (n = 9), emergency medical personnel (n = 8), physically disabled people (n = 6), and pregnant women (n = 6). Out of 26 responses to the question regarding current level of enforcement, 42.3% felt enforcement was “very good or good” and 57.7% characterized it as “fair or poor”. CONCLUSIONS: This study represents one of the largest international traffic law surveys reported. Most national seatbelt laws offer perilous exemptions to a broad array of vehicle types and road user groups. These findings, coupled with concern over the level of enforcement in the majority of countries surveyed, suggest that international road safety efforts have a long way to go to improve coverage and enforcement of national seat belt laws.